Prediction of tuberculosis cases based on sociodemographic and environmental factors in gombak, Selangor, Malaysia: A comparative assessment of multiple linear regression and artificial neural network models - Nur Adibah Mohidem; Malina Osman; Farrah Melissa Muharam; Saliza Mohd Elias; Rafiza Shaharudin; Zailina Hashim (Wolters Kluwer Medknow Publications, 2024)
Int J Mycobacteriol [serial online] 2021 [cited 2022 Dec 28];10:442-56